Sustainability Analysis of Oil Palm Plantations on Peatland in Rawa Bangun Village, Mukomuko Regency - Wulan Sari Ramadhanti; Ridha Rizki Novanda; Gita Mulyasari; Dian Adi Anggraini Elisabeth (Universitas Muhammadiyah Malang, 2025)
Oil palm is a key commodity that significantly contributes to the economy of Rawa Bangun Village, where most of the population relies on oil palm farming. In this area, peatlands over 3 meters deep are utilized for oil palm plantations, often in degraded conditions with limited nutrient availability, posing challenges for cultivation. This study assesses the sustainability index and status of oil palm plantations on peatlands across five dimensions: economic, social, institutional, and technological, using the Multidimensional Scaling (MDS) method. The findings revealed a sustainability index of 57.26%, categorized as